HOW TO FIND RESONANCE WOOD? - Bаrdarov, Nikolay; Minkovski, Nikolai (Innovation in Woodworking Industry and Engineering design, 2025)
Wood is widely used to produce sound emitters (decks) of musical instruments. This wood is called resonant. Although this name does not accurately reflect the physical nature of the phenomena occurring in wood when used in musical instruments, it is widely used in practice and in technical literature. The article examines the parameters that make a wood resonant. It is suggested that wood should be tested only when it meets part of the requirements and does not have good sound qualities. In this way, the influence of one or several factors can be isolated, and their importance on the quality of the wood can be determined.